Potential of Cari Rumah Software to Brings House Product Consumer and Digital Marketing Tool - Agus Pribadi (Universitas Bumigora Mataram-Lombok, 2022)
Growth of residential areas in the city of Mataram and its surroundings has a tendency to continue to increase. The growth of residential areas is in line with population growth which reaches 1,842%. Emergence of new residential areas in the city of Mataram and its surroundings involve a lot of amount of housing developer companies. Wide distribution of new residential/housing areas has in potential consumers having to make special efforts to obtain information on the purchase of new house. Cari Rumah software provides online search services for new residential products to the public using smartphone devices. The software makes it easier for prospective consumers to get information on new residential products without having to go to the marketing office of housing developer companies one by one. On the other hand, Cari Rumah software can also function as a means of marketing new residential house products by housing developer companies. Cari Rumah software offers convenience in finding new residential house product provided by housing developer companies. The content owned by the Cari Rumah software has the possibility as a means of digital marketing in addition to the function of helping potential consumers. This search study aims to find out the potential of the Cari Rumah software to meet the information needs of potential consumers and possibilities be used as a means of digital marketing. Method used is an impression test of the Cari Rumah software. The main stages of this method are gathering information, impression test, and potential conclusion. Results obtained indicate that the Cari Rumah software is not sufficient to meet the information needs for users / potential consumers of residential house product. However, 83.94% of users of the Cari Rumah software recommend to developer criteria features. Potential use of the Cari Rumah software as a digital marketing tool only reaches 20.15%.